PENERAPAN MEDIA POWER POINT MENGGUNAKAN CANVA PADA KELAS V SD NEGERI NO 173642 HASAHATAN - Susanti, Dewi Afriany; Aprianti, Seli; Purba, Renata Enalia; Kacaribu, Via Saberina (Jurnal Curere, 2024)
This research aims to determine the effect of applying Power Point media using the Canva application to improve learning outcomes in PKN lessons for students at state elementary school No. 173642 Hasahatan, even semester of the 2023/2024 academic year. The type of research is descriptive research with a library study method, which is obtained from several literatures related to the problem being researched. The research sample consisted of 24 field trials conducted on students using student response questionnaire sheets. Based on the calculation results, the highest average percentage of students' trials was the SL percentage (very feasible) with a percentage gain of 90.23%. So electronic-based learning media from student trials was declared very suitable for use to help teachers solve problems in understanding students' teaching materials. at SD No. 173642 Hasahatan.